PENGARUH INTENSITAS MODAL, INTENSITAS PERSEDIAAN DAN KEBIJAKAN UTANG TERHADAP AGRSIVITAS PAJAK: AGRESIVITAS PAJAK - Alfiatun Nurkhasanah (Yayasan Kayyis Mulia Jaya, 2024)
This research aims to obtain empirical evidence about the influence of capital intensity, inventory intensity and debt policy on tax aggressiveness. This type of research uses quantitative research using secondary data in the form of company annual reports taken from the energy sector listed on the Indonesia Stock Exchange for the period 2018 to 2022. The sampling method uses purposive sampling. The sample contained in this research was 70 data. Researchers used panel data regression techniques to test research data using eviews 12 as a statistical tool. The results of data analysis show that simultaneously capital intensity, inventory intensity and debt policy influence tax aggressiveness. Partially, the research results show that capital intensity has an effect on tax aggressiveness, while inventory intensity and debt policy have no effect on tax aggressiveness. Keywords: Tax Aggressiveness, Capital Intensity, Inventory Intensity, Debt Policy.